Law Enforcement Problems in Handling 2019 General Election Crimes by Gakkumdu - Darmawati, Darmawati; Tajuddin, Mulyadi Alrianto; Hadi, Firman (Faculty of Law, Universitas Pattimura, 2022)
Introduction: Law enforcement of the 2019 election crime is mandated by Law Number 7 of 2017 concerning Elections carried out by the Gakkumdu Party.Purposes of the Research: The purpose of this study is to find out the problematic forms of law enforcement for the 2019 general election crime in Gorontalo City, and to determine the factors that influence law enforcement for the 2019 general election crime law in Gorontalo City.Methods of the Research: The writing method used is empirical normative with a case approach obtained directly from the object of research in the field. The location of this research is the Integrated Law Enforcement Center at the Bawaslu of Gorontalo City.Results of the Research: The results of the study show that law enforcement for the 2019 general election crime in the city of Gorontalo is less than optimal, it can be seen that there are still findings/reports that have been discontinued and even cases have been dismissed from their investigations. As for the obstacles or influencing law enforcement, namely the lack of personnel in handling election crimes, the rules regarding election crimes have not been able to accommodate all forms of election crimes due to the development of new forms of election crimes and in terms of community culture who do not understand the rules regarding criminal acts election crime.